2019
DOI: 10.1093/bmb/ldz022
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and policy issues raised by uterus transplants

Abstract: Abstract Introduction In 2014, Brännström and colleagues reported the first human live birth following uterine transplantation (UTx). Research into this treatment for absolute uterine factor infertility has since grown with clinical trials currently taking place across centers in at least thirteen countries worldwide. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 45 publications
0
42
0
3
Order By: Relevance
“…In 2014, Brännström et al reported the first human live birth following UTx, arousing interest in research on UTx as AUFI treatment and resulting in at least 20 clinical trials and even more animal experiments currently taking place across the world [5]. The need for UTx is growing in addition to the increasing number of successful clinical trials worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Brännström et al reported the first human live birth following UTx, arousing interest in research on UTx as AUFI treatment and resulting in at least 20 clinical trials and even more animal experiments currently taking place across the world [5]. The need for UTx is growing in addition to the increasing number of successful clinical trials worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario would minimally have to grapple with issues concerning informed consent for obtaining the uterus, concerns regarding instrumentalization of the donor, and questions about who can donate (only patients undergoing hysterectomy for medical reasons, or healthy donors as well?). The use of living donors in the context of uterus transplantations (UTx) has brought along similar concerns for the welfare of donors and respect for their autonomy, but statements have been made that it can be justified if valid and informed consent is given by the donor (after thorough counseling); if levels of harm are proportionate to the benefits and fall below an accepted threshold; and if attempts are made to minimize the use of living donors and any harms inflicted to them [ 49 ]. A variant of using donated uteri for ectogenesis, is so-called xenopregnancy where an embryo or fetus is placed inside a uterine carrier belonging to a different species [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
“…This view, however, elides some difficult questions about how best to respect and promote autonomy in the context of UTx. In the case of both recipients and living donors, there is at least some risk that external pressures, such as coercion or pressure from family members to pursue UTx, or interpersonal pressures to donate one's uterus, might render consent less than fully voluntary [ 13 ]. At the same time, it might be asked whether broader social factors—specifically, pro-natalist ideology and associated social pressures—might pose a threat to autonomous consent.…”
Section: Autonomymentioning
confidence: 99%
“…When it comes to eligibility, some particular points of controversy are whether UTx should be offered to women who are genetically XY, women in same-sex relationships (where the other party does not have AUFI), and women who are already mothers [ 5 , 7 , 15 ]. It might further be asked whether UTx should be made available to men (either publicly or privately) on the grounds that they, too, lack a functional uterus and are in this sense subject to AUFI [ 13 ].…”
Section: Justicementioning
confidence: 99%